Immunoinformatics designing of peptide-based vaccine for malaria infection - Ogunniran, James Akinwumi; Oladipo, Elijah Kolawole; Ademola, Kemiki Olalekan; Imolele, Anthony Godswill; Alao, Olaoluwa Kehinde; Ajayi, Kehinde Oluyemi; Ockiya , Michael Asebake; Taiwo , Oluseyi Rotimi; Omede , Caleb Enejoh; Nwosu, Samuel Nzube; Ogunwole, Adeola Christianah (Eclética Química, 2025)
Malaria, a life-threatening disease prevalent in tropical regions, primarily affects infants, children under five, pregnant women, travelers, and individuals with HIV/AIDS. This study utilized an immunoinformatics approach to design a peptide-based malaria vaccine targeting antigenic proteins, including Apical Membrane Antigen 1, Knob-Associated Histidine-Rich Protein, Merozoite Surface Protein 1, and Sporozoite Surface Protein 2. Antigenic protein sequences were screened for antigenicity, allergenicity, toxicity, and immune responses involving CTLs, B-cells, and HTLs. Selected epitopes were linked with appropriate linkers and an adjuvant to enhance immunogenicity, forming a vaccine construct. The construction, comprising 1473 amino acids, exhibited a molecular weight of 15.21 kDa, a theoretical pI of 8.94, an aliphatic index of 60.01, and an instability index of 31.66, indicating stability. It was hydrophilic (GRAVY: –0.385) with favorable half-lives in mammalian, yeast, and E. coli systems. Docking studies showed strong binding affinity to human TLR2 and TLR4. In silico cloning indicated a CAI value of 0.92 and a GC content of 59.31%. Further studies are needed to validate its efficacy and safety.